Representación lingüística del concepto de persona en los sub-dialectos rusos de los veteranos yakutianos - Egorovna Zhondorova, Galina (2019)
This article studies some aspects of the linguistic worldview of the Yakutian old-timers and reveals the concept of person. Since the early 17th century, the Russian old-timers have been allegedly living among foreign languages in the Arctic territory of the Republic of Sakha (Yakutia) which is the largest subject of the Russian Federation. Old-timers are the oldest group of the Russian population living in Siberia. The study is based on the folklo- re and dialectal materials collected from representatives of this ethnic group and reflected in the "Dictionary of the Russian sub-dialects of the Yakutian old-timers". The authors of the article focus on the structure of the person concept, description of its main characteristics and identification of specific linguistic representation in the Russian sub-dialects used by old-timers. The semantics of this concept is closely connected with the peculiar lifestyle of the Yakutian old-timers. Este artículo estudia algunos aspectos de la cosmovisión lingüística de los veteranos yakutianos y revela el concepto de persona. Desde princi-pios del siglo XVII, los veteranos rusos supuestamente viven entre lenguas extranjeras en el territorio ártico de la República de Sakha (Yakutia), que es el tema más importante de la Federación Rusa. Los veteranos son el grupo más antiguo de la población rusa que vive en Siberia. El estudio se basa en el folclore y los materiales dialectales recopilados de representantes de este grupo étnico y reflejados en el "Diccionario de los sub-dialectos rusos de los veteranos yakutianos". Los autores del artículo se centran en la estructura del concepto de persona, la descripción de sus características principales y la identificación de la representación lingüística específica en los sub-dialectos rusos utilizados por los veteranos. La semántica de este concepto está estre-chamente relacionada con el peculiar estilo de vida de los veteranos yakutianos